POTENTIALITIES OF NEW TECHNOLOGIES IN THE TEACHING-LEARNING PROCESS IN BRAZILIAN PUBLIC SCHOOLS: A PARTICIPATING RESEARCH APPROACH - dos Santos Lins, Givaldo; da Silva, Alex; da Silva Lima, Almir; Cristina Souza, Maryone; do Nascimento Prado, Roselândia; Pinho Neto, Gisélia; da Silva Costa, Joselma; Afonso Alves Geronimo, Manuel; Santos Costa, Roseane; Januária da Silva Araujo, Silvia (Revista Gênero e Interdisciplinaridade, 2024)
This article discusses the potential of new technologies in the teaching-learning process in Brazilian public schools, using participatory research to investigate how these technologies can be integrated into the educational environment. With the aim of exploring these possibilities, the study analyzes the implementation of digital tools, such as Linux Educacional, and programs that encourage technological inclusion in public schools. The use of blogs and social networks is highlighted as a means to create a more engaging and interactive learning environment. The discussion suggests that despite these difficulties, the planned and strategic incorporation of ICTs can transform education, offering a richer and more contextualized experience for students and teachers. Furthermore, the need for effective public policies and continuous support to ensure that technologies are used efficiently is emphasized. Although there are obstacles to be overcome, the potential of new technologies to enrich the educational process is considerable, justifying efforts to overcome barriers and promote more innovative and motivating education in Brazilian public schools.